Providing Security in Data Aggregation using RSA algorithm (INTERNATIONAL JOURNAL OF COMPUTERS & TECHNOLOGY, 2012)
The RSA algorithm proposed by Rivest, Adi Shamir and Leonard Adleman is cryptography technique. The current problem with wireless sensor network is how to protect theÂ  security of the sensor data. RSA algoritm is used as a digital signature authentication in the field of security, basically works on deciding encryption variable. In this also the basic concept is to decide a description variable and then decide the description variable using same encryption variable. It is a secure and fast cryptographic system. The major effort will be applied on the RSA encryption technique in order to make node authenticated as well as to secure data while dealing with aggregation.